THE JUDICIAL COMMISSION'S AUTHORITY TO SUPERVISE THE ETHICAL BEHAVIOR OF JUDGES ON SOCIAL MEDIA - Afkar Raihan Winfy Harahap; Farid Wajdi (Inspiring Law Journal, 2026)
This study discusses the Judicial Commission's role in supervising the ethical behavior of judges on social media. In today's digital era, many people indirectly use social media inappropriately. Law enforcement officers, especially judges, are trusted by the Indonesian people. The Judicial Commission must supervise judges to create a good and clean image of the judiciary in the eyes of the public. The Judicial Commission has the primary authority to supervise the ethical behavior of judges, including on social media. According to Law Number 18 of 2011, to prevent the decline of the dignity of the judiciary, which can intentionally or unintentionally make judges violate their code of ethical behavior on social media. Therefore, the Judicial Commission's supervision of social media is essential to prevent the decline of the dignity of the judiciary due to judges' bad behavior on social media. Public trust and judges' ability to maintain judicial integrity are crucial.            The type of research used in this thesis is normative legal research. This normative legal research method focuses on the study of applicable legal norms or rules. This method is often used in research in the field of law or other sciences related to certain norms or rules. The results of this research are the limits of the Judicial Commission's authority in overseeing the ethical behavior of judges on social media, which is only focused on monitoring judges' activities on social media, conducting verification and closed investigations, and proposing sanctions to the Supreme Court.            The Judicial Commission does not have the authority to interfere in the substance of decisions or the judicial process to maintain judicial independence. Forms of judicial behavior on social media that could be considered a violation of the code of ethics include posting statuses or comments that are racially and ethnically sensitive, open support for certain candidates, and inappropriate content that demeans the dignity of the people. Therefore, strengthening the role of the Judicial Commission through specific regulations, digital ethics guidelines, and synergy with the Supreme Court is crucial to maintaining the integrity and authority of the judiciary in the social media era.